LH and prolactin secretion under constant light in estrogen treated rats (Revista Española de Fisiología, 1979)
Plasma LH and prolactin levels were studied in ovariectomized adult female rats submitted to light-darkness (L:D) or constant light (L:L) schedules, after the administration of estradiol benzoate (EB), 75 micrograms/day for six consecutive days. Previous to the treatment with EB LH levels were lower and prolactin levels higher in the L:L females. On days 1 and 2 after treatment, L:D females showed circadian variations of LH levels, these being higher at 17 h than at 10 h. This pattern disappeared in the L:D females. Prolactin levels increased similarly in both groups. Nine days after treatment, plasma prolactin levels remained high and the circadian pattern of LH in the L:D group disappeared.